(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
As the educational process continues to develop, ensuring the simplicity, convenience, and effectiveness of modern teaching methods has become increasingly important. In today’s context, the use of multimedia tools in pedagogical activity makes the learning process more dynamic, engaging, and effective. Utilizing multimedia opportunities in organizing lessons step by step enhances students’ ability to acquire knowledge, reinforce it, and develop creative thinking skills. The proper use of multimedia at each stage of the lesson provides a professional approach for the teacher and leads to strong motivation and better outcomes for students.